Pengaruh Air Rebusan Biji Alpukat (Persea americana L.) Terhadap Kadar Gula Darah Mencit (Mus musculus Mill.) Diabetesi Yang Diberi Diet Beras Warna - Wahyuni, Dwi; Sudiastuti, Sudiastuti; Sudrajat, Sudrajat (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This study was undertaken to investigate the effect of the seed avocado cooking water on lowering blood sugar levels in aloxan-diabetic mouse which has diet of black or red rice. The seed avocado cooking water was administered orally and the blood glucose level was measured weekly for 3 week. The research used a design random complete with 24 male then divided into 6 groups to be treated.The hypoglycaemic activity was evaluated by comparing with the initial blood glucoce level. In aloxan-diabetic mouse, the seed avocado cooking water and diet black or red rice showed their influence to decrease blood sugar levels between 42.72% s.d. 51.06%.The variation of combine the composition diet showed no difference in the effect of a decrease in blood sugar levels